Envelhecimento acelerado em sementes de Eucalyptus grandis Hill ex Maiden classificadas por tamanho - Nakagawa, João [UNESP] (2001)
Two experiments of seed ageing of Eucalyptus grandis Hill ex Maiden were carried out at laboratory conditions. In the first experiment, two seed lots were classified in two square mesh screens (< 0.84 to ≥ 0.71 mm and < 0.71 mm to ≥ 0.59 mm), submitted to 42 °C and 100% relative humidity, for 0, 8, 12, 24, and 32 hours of stress treatments. Seed germination tests were done with just aged seeds. The results showed that the stress period was not sufficient for ageing the seeds. In the second experiment, the best quality seed lot was separated in the same two sizes. The seeds were submitted under the same stress conditions of the first experiment but for 0, 48, 72, and 96 hours. The germination test was done right after the seeds were taken from the stress conditions, and with stored seeds at dry chamber (2 weeks and 26 months). It was concluded that both seed sizes reached 30% of moisture content under 72 hours of ageing conditions and showed significant germination losses when compared with seeds without ageing (control), as the moist seeds as the stored ones at dry chamber, for both 2 weeks and 26 months.